Design, construction and testing of various reactor geometries for gas-phase photocatalytic carbon dioxide reduction - Rezqalla, Batool Abdalla. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
This thesis proposes a comprehensive preliminary design of a gas- phase photocatalytic carbon dioxide reduction system with water. The aim was to design, construct and operate a reaction system using titania-based photocatalytic materials and various sources of light. To accomplish this, the lab-scale process system was constructed from scratch, which was followed by calibration of the equipment, synthesis of the photocatalyst material, and initial operation of the process as a whole under varying operating conditions. The main operational variables were the type of light source, the weight of photocatalyst, the inlet gas flowrates and the water heating of the water bubbler, which was used to generate moisture and transport it with CO2 into the system. The reactions were carried out over photocatalysts containing single (Pt or Cu) and bimetallic (Pt + Cu) co-catalyst loading onto TiO2 with or without coating with ionic liquid after metal loading. Two tubular and one balloon photoreactor geometries were tested, and the balloon photoreactor geometry proved to be the most effective. Syngas was obtained as the main product using the single metal photocatalysts, while syngas and methane were obtained using the bimetallic photocatalyst. Using single metal loaded TiO2, the maximum product yield obtained was 11.79 (with Pt) and 83.72 μmol/(h.gcat) (with Cu) for H2 and CO, respectively. With the bimetallic photocatalyst, those values increased to 164.76, 1757.29, and 60.26 μmol/(h.gcat) for H2, CO, and CH4, respectively. Establishing better gas-photocatalyst contact in the photoreactor design and enhancing the properties of the photocatalyst by applying various modifications were proposed for future studies to further improve the system performance.
Keywords: Photocatalysis.; Carbon dioxide.; Reduction (Chemistry)